THE EVOLUTION OF THE OFFICIAL SOVIET VIEW ON THE HUNGARIAN EVENTS OF 1956 - A. Stykalin (Гуманитарные и юридические исследования)
The author concentrates on the evolution of the Soviet official view on the Hungarian events of 1956 in the years of Gorbachev’s “perestroika” in connection with the crash of Communism in Central-Eastern Europe.